Xiaoyin-anshen formula alleviates psoriasis complicated by sleep disturbances by regulating melatonin, antioxidant enzymes, and pro-inflammatory cytokines in mice - Zhu, Zebing; Yin, Qiang; Duan, Xingwu (Frontiers in Pharmacology, 2024)
Psoriasis is a common autoimmune and chronic inflammatory dermatological disease that is mainly associated with aberrant immune response and oxidative stress(OS).OS,a crucial pathogenic factor in psoriasis,contributes to psoriasis-like inflammation mediated by the IL-23/IL-17 inflammatory axis.Sleep disturbances (SDs),highly prevalent in patients with psoriasis,exacerbate the condition by disrupting circadian rhythms and reducing melatonin levels,thus promoting OS and inflammation.Xiaoyin-Anshen formula(XYAS),a traditional Chinese medicine (TCM) formula,is composed of the Liangxue-Jiedu(LXJD) and Qingxin-Anshen(QXAS) compounds and has been demonstrated to be effective in treating psoriasis complicated by SDs.However, its exact pharmacological mechanism remains uncertain.This study aimed to verify whether XYAS can exert therapeutic effects on the disease by regulating melatonin (MLT), protecting against OS, and inhibiting inflammation.A combined psoriasis and SDs mouse model was established by smearing 62.5mg of 5%imiquimod(IMQ) cream for 7 consecutive days,along with a daily injection of p-chlorophenyl alanine(PCPA) solution at a dosage of 300 mg/kg at days 6-7.Mice were randomly divided into groups:control,model,MLT,XYAS,LXJD,QXAS.Each group was treated according to its designation at days 8-14,receiving either an oral gavage of XYAS/LXJD/QXAS solution at a dosage of 2 ml/100g per day,or a daily injection of MLT solution at a concentration of 0.25 mg/ml,with a dosage of 5mg/kg.Immunohistological analysis,pentobarbital-induced sleep test,western blotting,and enzyme-linked immunosorbent assay(ELISA) were performed to assess and compare pathological features,sleep conditions,localization and/or levels of manganese-dependent superoxide dismutase(mnSOD),mitochondrial cytochrome c(Cyt-C),MLT,retinoid-related orphan nuclear receptor-α(RORα),pro-inflammatory cytokines interleukin(IL)-6,IL-17A,and tumor necrosis factor-alpha(TNF-α) among groups.RESULTS:MLT,XYAS,LXJD,and QXAS exhibited varying therapeutic effects on RORα regulation,OS inhibition,mitochondrial protection,and anti-inflammation.Compared to the model,the lesion severity/thickness and serum IL-6,IL-17A,TNF-α levels were gradually reduced in groups MLT,QXAS,LXJD,and XYAS.However,no statistical difference identified in TNF-α levels between groups MLT and model. Additionally, skin MLT levels gradually increased in the MLT,QXAS,and XYAS groups,while RORα levels gradually increased in the MLT,QXAS,LXJD,andXYAS groups.All treatments increased mnSOD and reduced Cyt-C levels in skin lesions,with XYAS showing the most significant changes.(1)Improving melatonin-RORα axis in the skin can lead to an increase in mnSOD and a reduction in Cyt-C levels,which provide protection against OS, mitochondrial damage, and psoriatic inflammation.(2)Reducing IL-6,IL-17A,and TNF-α to suppress IL-23/Th17 pro-inflammatory signaling and epidermal hyperplasia in psoriasis.